2013
DOI: 10.1016/j.agee.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The potential of organic fertilizers and water management to reduce N2O emissions in Mediterranean climate cropping systems. A review

Abstract: International audienceEnvironmental problems related to the use of synthetic fertilizers and to organic waste management have led to increased interest in the use of organic materials as an alternative source of nutrients for crops, but this is also associated with N2O emissions. There has been an increasing amount of research into the effects of using different types of fertilization on N2O emissions under Mediterranean climatic conditions, but the findings have sometimes been rather contradictory. Available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
175
5
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(216 citation statements)
references
References 163 publications
16
175
5
4
Order By: Relevance
“…The type of fertilizer does not seem to represent a driver of the yield gap between organic and conventional production that we found, as other studies under Mediterranean conditions have shown that yields are not affected by fertilizer type and could even be increased by the presence of organic inputs (Palese et al 2013; see also Aguilera et al 2013b). Therefore, there is a need for more research in order to close this yield gap; e.g., in irrigated organic fruits, this gap is mainly due to pest and disease problems, which are not well controlled.…”
Section: Bridging the Yield Gapsupporting
confidence: 65%
See 1 more Smart Citation
“…The type of fertilizer does not seem to represent a driver of the yield gap between organic and conventional production that we found, as other studies under Mediterranean conditions have shown that yields are not affected by fertilizer type and could even be increased by the presence of organic inputs (Palese et al 2013; see also Aguilera et al 2013b). Therefore, there is a need for more research in order to close this yield gap; e.g., in irrigated organic fruits, this gap is mainly due to pest and disease problems, which are not well controlled.…”
Section: Bridging the Yield Gapsupporting
confidence: 65%
“…Reduced fossil energy consumption in organic orchards (Guzmán and Alonso 2008;Alonso and Guzmán 2010) suggests that there may also exist greenhouse gas emissions savings in these systems, taking into account the high importance of energy-related emissions in the carbon footprint of herbaceous Spanish cropping systems . At the soil level, evidence suggests low N 2 O emissions associated to organic fertilizers (Aguilera et al 2013b) and higher soil organic carbon (SOC) stocks in organically managed soils under Mediterranean climate (Aguilera et al 2013a). All these features point to a large mitigation potential of Mediterranean fruit tree orchards and particularly of organic agro-ecosystems, but comprehensive assessments of their global warming potential are very scarce.…”
Section: Introductionmentioning
confidence: 99%
“…However, this strategy is only applicable in certain developed areas with nutrient surpluses. Another recent work shows a decrease in N 2 O emissions when using organic fertilizers in comparison with the use of synthetic products in dryland areas (Aguilera et al 2013b).…”
Section: Adoption Of More Efficient Water Management Practicesmentioning
confidence: 99%
“…All emission data were additionally compared with ammonium nitrate (AN) in FG. These data were gathered from a meta study comparing different irrigation systems (drip, furrow, rainfed) in Mediterranean climates (Aguilera et al 2013b). Production of the irrigation equipment and its transportation was not taken into account, because it was assumed that FG only takes place in regions were irrigation is a standard measure in all cultivation systems.…”
Section: Stabilized Nitrogen Fertilizermentioning
confidence: 99%
“…Irrigation is mostly applied during summer periods when soil temperature, and due to irrigation also the soil moisture conditions for N 2 O production after fertilizer application, are more favourable (Jambert et al 1997, Hao et al 2001, Scheer et al 2008, Aguilera et al 2013b) and therefore a strong stimulation of the N 2 O fluxes might occur. Adapting nitrogen supply closely to crop nitrogen demand during the vegetation period and thereby lowering nitrogen peaks in the soil might be the most important reason for overall lower N 2 O emission via fertigation.…”
mentioning
confidence: 99%